2020
DOI: 10.1371/journal.ppat.1008332
|View full text |Cite
|
Sign up to set email alerts
|

Host-glycan metabolism is regulated by a species-conserved two-component system in Streptococcus pneumoniae

Abstract: Pathogens of the Streptococcus genus inhabit many different environmental niches during the course of an infection in a human host and the bacteria must adjust their metabolism according to available nutrients. Despite their lack of the citric-acid cycle, some streptococci proliferate in niches devoid of a readily available carbohydrate source. Instead they rely on carbohydrate scavenging for energy acquisition, which are obtained from the host. Here we discover a two-component system (TCS07) of Streptococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 83 publications
2
23
0
Order By: Relevance
“…When colonizing the mucosal surface of the human host, which is a glucose‐deplete environment, GAS will need to utilize alternative carbon sources for proliferation. As mannose is typically available in glycans of host proteins decorating the surface of cells, as well as a component of host mucins, it could be available as a carbon source to sustain cellular viability upon degradation (Andreassen et al., 2020) by GAS that are colonizing the mucosal surface. Thus, the presence of mannose could signal to GAS that it is in a host environment that is suitable for colonization, resulting in the promotion of biofilm formation mediated through the QS system (Gogos et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When colonizing the mucosal surface of the human host, which is a glucose‐deplete environment, GAS will need to utilize alternative carbon sources for proliferation. As mannose is typically available in glycans of host proteins decorating the surface of cells, as well as a component of host mucins, it could be available as a carbon source to sustain cellular viability upon degradation (Andreassen et al., 2020) by GAS that are colonizing the mucosal surface. Thus, the presence of mannose could signal to GAS that it is in a host environment that is suitable for colonization, resulting in the promotion of biofilm formation mediated through the QS system (Gogos et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that the TCS YesMN impacts pneumococcal shedding, we constructed mutants with unmarked, in-frame deletion of HK yesM ( ΔyesM ), the RR yesN ( ΔyesN ), or both yesMN ( ΔyesMN ). Deletion of yesMN was not associated with impaired growth (18) and all the constructed mutants in the study grew as WT type 4 isolate (data not shown).…”
Section: Resultsmentioning
confidence: 85%
“…Overexpression of the response regulator (RR) YesN in D39 (Type 2 isolate) leads to an increase in the expression of genes that code for N-linked glycan-metabolizing enzymes. Also, compared to the parental D39, ΔyesMN had a slightly reduced virulence in a lung infection model (18).…”
Section: Resultsmentioning
confidence: 99%
“… d Member of the WalRK two-component system regulon ( 55 ). e Member of the TCS07/YesMN two-component system regulon ( 84 ). f Member of the LiaFSR two-component system regulon ( 58 ).…”
Section: Resultsmentioning
confidence: 99%